Roadbed soil cement cementing material curing agent and use method thereof
By using a cement cementitious material curing agent containing a modified anti-seepage enhancer in the roadbed soil, the stability and permeability problems of traditional cement-based materials when used in acidic soil are solved, and higher soil consolidation strength and durability are achieved.
Patent Information
- Application Number
- CN202510559602.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2025-06-03
- Estimated Expiration
- 2045-04-30
AI Technical Summary
When traditional silicate cement-based materials are used in acidic soil, the hydrated products are prone to erosion, resulting in unstable soil consolidation, decreased strength, and insufficient permeability, affecting the stability of the roadbed.
A roadbed soil cement cementitious material curing agent is used, which includes silicate cement, coal gangue particles, fly ash, silica fume, anti-seepage enhancer, water reducing agent and fiber. The anti-seepage enhancer forms a colloid of aluminum hydroxide by modifying the combination of polymeric aluminum sulfate and hydrophobic agent, and coats the hydrophobic agent to improve the anti-seepage performance of the soil solidified body.
This curing agent effectively reduces the adverse effects of acidic soil on soil consolidates, improves the strength and stability of the consolidates, and significantly improves the permeability resistance, thereby extending the service life of the soil consolidates.
Smart Images

Figure CN120081637A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cement-based soil solidifying agents, and particularly relates to a roadbed soil cementitious material solidifying agent and a using method thereof. Background Art
[0002] Disclosing the information of this background art section is only intended to increase the understanding of the overall background of the present invention, and is not necessarily regarded as an admission or any form of implication that this information constitutes the prior art already known to those of ordinary skill in the art.
[0003] The reinforcement treatment of roadbeds is a very important link in engineering construction, especially for roadbed projects such as highways and railways that need to be built on soft soil layers. One of the currently adopted methods is the soil solidification technology, that is, a solidifying agent is incorporated into the soil, and the cementing and solidifying effect of the solidifying agent is used to improve the strength and bearing capacity of the soil layer. The silicate cement-based material is one of the commonly used soil solidifying agents. After being incorporated into the soil, the cementitious components formed by reacting with water can realize the rapid cementing and hardening of loose soil.
[0004] However, for acidic soils, when using cement-based materials for solidification, there is a phenomenon that the hydration products of cement are easily eroded and damaged, resulting in unstable soil solidified bodies and decreased strength. This is because a large amount of calcium hydroxide is contained in the hydration products of traditional silicate cement-based materials in the soil, and its acid resistance is poor. When encountering acidic soil, it is easily eroded and dissolved, and gradually loses after forming soluble substances, resulting in an increase in the porosity of the soil solidified body, a decrease in strength, and a reduction in stability. In addition, the soil solidified body formed by using traditional silicate cement-based materials also has the problem of insufficient impermeability, and leakage is likely to occur during service, affecting the stability of the roadbed. Summary of the Invention
[0005] Aiming at the above problems, the present invention discloses a roadbed soil cementitious material solidifying agent and a using method thereof, which not only reduce the adverse effects of acidic soil on the stability of the formed soil solidified body, but also improve the impermeability, thereby being beneficial to improving the durability of the soil solidified body. Specifically, the technical solution of the present invention is as follows.
[0006] First, the present invention discloses a roadbed soil cementitious material solidifying agent, which comprises the following components: 200-275 parts by weight of portland cement, 130-160 parts by weight of coal gangue particles, 280-400 parts by weight of fly ash, 100-142 parts by weight of silica fume, 60-78 parts by weight of impermeability enhancer, 3-6.5 parts by weight of water reducer, and 25-40 parts by weight of fiber. The impermeability enhancer is prepared by the following method: (1) Disperse the polyaluminum sulfate powder into absolute ethanol, then add a silane coupling agent and a water repellent, and heat and keep warm under stirring conditions. After completion, separate the solid to obtain the modified polyaluminum sulfate.
[0007] (2) Add the modified polyaluminum sulfate to water and heat and keep warm under stirring conditions. After completion, evaporate to dryness to remove the water, and the anti-seepage and strengthening agent is obtained.
[0008] Further, in step (1), the ratio of the polyaluminum sulfate powder to absolute ethanol is 1 g: 20 - 30 ml. Optionally, the fineness of the polyaluminum sulfate powder is 100 - 200 mesh.
[0009] Further, in step (1), the silane coupling agent is 0.15 - 0.3% of the mass of the polyaluminum sulfate powder. Optionally, the silane coupling agent includes at least one of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, etc.
[0010] Further, in step (1), the water repellent is 0.5 - 0.8% of the mass of the polyaluminum sulfate powder. Optionally, the water repellent includes at least one of tridecafluorooctyltrimethoxysilane, perfluorooctyltriethoxysilane, perfluoroalkylsiloxane, heptadecafluorodecyltriethoxysilane, hexamethyldisilazane, etc.
[0011] Further, in step (1), the heating temperature is 60 - 70 °C, and the heat preservation time is 1 - 1.5 hours.
[0012] Further, in step (2), the ratio of the modified polyaluminum sulfate to water is 1 g: 5 - 10 ml.
[0013] Further, in step (2), the heating temperature is 40 - 60 °C, and the heat preservation time is 10 - 20 min.
[0014] Further, in step (2), the evaporation temperature is 80 - 100 °C, and it is evaporated to dryness at this temperature until the weight of the remaining solid product no longer changes.
[0015] Further, the coal gangue particles are treated by the following method: Calcinate the granular coal gangue, then immerse it in a sodium silicate solution, and then separate the solid particles and dry them to obtain.
[0016] Further, the calcination temperature is 700 - 850 °C, and the time is 30 - 45 min.
[0017] Furthermore, the ratio of the granular coal gangue to the sodium silicate solution is 1 g: 5 - 20 ml. Optionally, the mass fraction of the sodium silicate solution is 4 - 10%.
[0018] Furthermore, the impregnation time is 1 - 2 hours. Optionally, the particle size distribution of the coal gangue microparticles is between 1 - 5 mm.
[0019] Furthermore, the fibers include at least one of polyethylene fiber, polypropylene fiber, polyvinyl alcohol fiber, polyacrylonitrile fiber, etc. Optionally, the length of the fibers is 10 - 25 mm. These fibers help to further improve the strength and stability of the soil solidified body.
[0020] Furthermore, the water reducing agent includes at least one of polycarboxylate water reducing agent, naphthalene series water reducing agent, lignosulfonate water reducing agent, etc.
[0021] Secondly, the present invention discloses a method for using the roadbed soil cementitious material curing agent, which includes the following steps: mixing the dry acidic soil to be solidified with the curing agent evenly, and then adding water and mixing evenly.
[0022] Furthermore, the dosage of the curing agent is 20 - 30% of the mass of the soil to be solidified. The water is 42 - 48% of the total mass of the soil to be solidified and the curing agent. Optionally, the pH of the soil to be solidified is 5 - 6.5.
[0023] Compared with the prior art, the present invention has at least the following beneficial technical effects: When using ordinary Portland cement to solidify acidic subgrade soil, there are problems such as a decrease in the strength of the solidified body, a reduction in stability, and insufficient impermeability of the solidified body. The present invention effectively overcomes the above problems by adding an impermeability enhancer to the curing agent. To this end, the present invention first grafts a hydrophobic agent onto polyaluminum sulfate to form modified polyaluminum sulfate, and then adds it to water for hydrolysis reaction. The hydrophobic agent is coated therein by the cementing action of the formed aluminum hydroxide colloid to form an impermeability enhancer. After adding it to the soil curing agent, since the coating of the hydrophobic agent by aluminum hydroxide effectively reduces the influence on the hydration of Portland cement particles, the surface of the cement particles can be in full contact with the mixing water, thus ensuring the full progress of the hydration reaction, forming more cementitious components, and improving the strength of the soil solidified body. In addition, the aluminum hydroxide in the impermeability enhancer can also neutralize the hydrogen ions in the acidic soil and reduce the soil acidity. The initiation of the hydration reaction of cement requires a certain amount of time, which helps to prevent the problems of a decrease in the strength of the soil solidified body and a reduction in stability caused by the dissolution of calcium hydroxide, the hydration product of cement, by hydrogen ions in the acidic soil. At the same time, the hydrophobic agent is gradually released by the reaction of aluminum hydroxide with hydrogen ions in the impermeability enhancer. Since the surface of the cement particles has been in full contact with water at this time, the released hydrophobic agent can not only construct a hydrophobic system in the soil solidified body to improve the waterproof and impermeability ability of the soil solidified body, but also avoid the influence on cement hydration. Again, the aluminum ions formed after the reaction of aluminum hydroxide with hydrogen ions in the impermeability enhancer react with the calcium hydroxide solution, the hydration product of the subsequent hydration reaction, to reform aluminum hydroxide, which fills the pores of the soil solidified body and will not dissolve and be lost in water. This not only improves the density of the solidified body, thereby improving the waterproof and impermeability ability, but also helps to improve the strength of the solidified body.
[0024] In addition, in the present invention, the coal gangue aggregate in the curing agent is first calcined and then activated with a sodium silicate solution. This not only eliminates its adverse effect on the structural stability of the soil solidified body, but also can reduce the soil acidity, and improve the strength of the solidified body by participating in the hydration reaction itself. This is because the organic matter contained in the coal gangue aggregate is removed after high-temperature calcination, avoiding volume changes caused by the reaction of the organic matter in the coal gangue aggregate during the service process of the soil solidified body and affecting the structural stability of the solidified body. At the same time, the reaction activity of the coal gangue can be effectively improved after being treated with the sodium silicate solution, and it can carry out pozzolanic reactions with calcium hydroxide generated by the cement hydration reaction to form cementitious components such as calcium silicate hydrate and calcium aluminate hydrate, increasing the content of cementitious components in the soil solidified body, thereby improving the strength of the solidified body. In addition, the sodium silicate stored in the pores formed after the coal gangue aggregate removes the organic matter can react with hydrogen ions in the soil to form silicic acid, and the silicic acid neutralizes with the calcium hydroxide solution generated by the subsequent cement hydration to form calcium silicate precipitation, which fills the pores of the coal gangue and can play a densifying role, helping to improve the strength and impermeability of the coal gangue aggregate. In addition, the utilization and consumption of the hydration product calcium hydroxide in the above process also contribute to promoting the degree of cement hydration reaction and improving the strength of the soil solidified body. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The specification drawings forming a part of the present invention are used to provide a further understanding of the present invention. The schematic embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. Hereinafter, the embodiments of the present invention will be described in detail with reference to the drawings, where: Figure 1 Diagram of the anti-seepage enhancer sample prepared for Example 1 below.
[0026] Figure 2 Diagram of the compressive strength test of the solidified soil specimen prepared for Example 1 below.
[0027] Figure 3 Diagram of the anti-seepage performance test for Examples 1 to 6 below.
[0028] Figure 4 Diagram of the contact angle test of the solidified soil specimen for Example 1 below.
[0029] Figure 5 Diagram of the compressive strength test of the solidified soil specimen prepared for Example 2 below.
[0030] Figure 6 Diagram of the contact angle test of the solidified soil specimen for Example 2 below.
[0031] Figure 7 Diagram of the compressive strength test of the solidified soil specimen prepared for Example 3 below.
[0032] Figure 8 Compressive strength test diagram of the solidified soil specimens prepared for Example 4 below.
[0033] Figure 9 Compressive strength test diagram of the solidified soil specimens prepared for Example 5 below.
[0034] Figure 10 Compressive strength test diagram of the solidified soil specimens prepared for Example 6 below.
[0035] Figure 11 Compressive strength test diagram of the solidified soil specimens prepared for Example 7 below.
[0036] Figure 12 Anti-seepage performance test diagram of Example 7 and Example 8 below.
[0037] Figure 13 Compressive strength test diagram of the solidified soil specimens prepared for Example 8 below. Detailed implementation manners
[0038] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and not to limit the scope of the present invention. For the experimental methods without specific conditions noted in the following embodiments, they are generally carried out under conventional conditions or according to the conditions recommended by the manufacturer.
[0039] Unless otherwise defined, all professional and scientific terms used herein have the same meaning as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be obtained through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in the conventional manner in the art or according to the product instructions. In addition, any methods and materials similar or equivalent to the recorded content can be applied to the method of the present invention.
[0040] Example 1: The preparation of a roadbed soil cementitious material solidifying agent includes the following steps: (1) Add polyaluminum sulfate powder with a fineness of 180 meshes to anhydrous ethanol at a ratio of 1 g: 25 ml. After stirring evenly, add γ-aminopropyltriethoxysilane and trifluorooctyltrimethoxysilane, wherein: the γ-aminopropyltriethoxysilane is 0.22% of the mass of the polyaluminum sulfate powder, and the trifluorooctyltrimethoxysilane is 0.6% of the mass of the polyaluminum sulfate powder. Then heat to 70 °C and keep warm for 1 hour under continuous stirring. After completion, filter out the solid matter to obtain modified polyaluminum sulfate.
[0041] (2) Add the modified polyaluminum sulfate to water at a ratio of 1 g: 8 ml, then heat it to 50 °C with continuous stirring and keep it warm for 10 min. After completion, continue to heat it to 100 °C for evaporation to dryness until the weight of the remaining solid product no longer changes, thus obtaining the anti-seepage enhancer (as Figure 1 shown), and set it aside.
[0042] (3) First, calcine the crushed granular coal gangue at 800 °C for 35 min. After completion, cool it to room temperature. Mix the calcined product with a 7% sodium silicate solution by weight at a ratio of 1 g: 10 ml, stir evenly, and then impregnate for 1.5 hours. After completion, filter out the particulate matter and dry it at 100 °C until the weight no longer changes to obtain coal gangue microparticles with a particle size distribution between 2 and 5 mm, and set it aside.
[0043] (4) Weigh each component according to the following ratio: 237 parts by weight of 42.5 ordinary Portland cement, 145 parts by weight of the coal gangue microparticles of this example, 300 parts by weight of fly ash, 120 parts by weight of silica fume, 65 parts by weight of the anti-seepage enhancer of this example, 4 parts by weight of polycarboxylate superplasticizer, and 28 parts by weight of polypropylene fiber with a length of 25 mm. Mix the above components evenly by stirring to obtain the cementitious material curing agent.
[0044] In the dry soil to be solidified (pH = 5.87), incorporate 25% by mass of the cementitious material curing agent of this example. After stirring for 3 min, add 45% of the water by mass of the obtained mixed powder, and then continue to stir for 2 min. Pour the obtained solidified soil into a mold, and after hardening and demolding, cure it naturally for 28 d to obtain solidified soil specimens. Then test the compressive strength (as Figure 2 shown) and anti-seepage performance (as Figure 3 shown) of the solidified soil specimens. In addition, test the contact angle (as Figure 4 shown) of the solidified soil specimens. The larger the contact angle, the better the hydrophobic anti-seepage performance. The test results are shown in the following table: .
[0045] Example 2: The preparation of a subgrade soil cementitious material curing agent includes the following steps: (1) Add the polyaluminum sulfate powder with a fineness of 200 mesh to anhydrous ethanol at a ratio of 1 g: 30 ml, stir evenly, and then add γ-methacryloxypropyltrimethoxysilane and perfluorinated alkylsiloxane. Among them: the γ-methacryloxypropyltrimethoxysilane is 0.15% of the mass of the polyaluminum sulfate powder, and the perfluorinated alkylsiloxane is 0.5% of the mass of the polyaluminum sulfate powder. Then heat it to 60 °C with continuous stirring and keep it warm for 1 hour. After completion, filter out the solid matter to obtain the modified polyaluminum sulfate.
[0046] (2) Add the modified polyaluminum sulfate to water at a ratio of 1 g: 10 ml, then heat it to 40 °C under continuous stirring and keep it warm for 20 min. After completion, continue to heat it to 90 °C for evaporation to dryness until the weight of the remaining solid product no longer changes, thus obtaining the anti-seepage enhancer for standby.
[0047] (3) First, calcine the crushed granular coal gangue at 700 °C for 45 min, then cool it to room temperature after completion. Mix the calcined product with a 4% sodium silicate solution by weight at a ratio of 1 g: 20 ml, stir evenly, and then impregnate for 2 hours. After completion, filter out the particulate matter and dry it at 100 °C until the weight no longer changes to obtain coal gangue microparticles with a particle size distribution between 1 and 3 mm for standby.
[0048] (4) Weigh each component according to the following ratio: 275 parts by weight of 42.5 ordinary Portland cement, 160 parts by weight of the coal gangue microparticles of this example, 400 parts by weight of fly ash, 142 parts by weight of silica fume, 78 parts by weight of the anti-seepage enhancer of this example, 6.5 parts by weight of naphthalene-based water reducer, and 40 parts by weight of polyvinyl alcohol fiber with a length of 10 mm. Mix the above components evenly by stirring to obtain the cementitious material curing agent.
[0049] Incorporate 30% by mass of the cementitious material curing agent of this example into the dry acidic soil to be cured (pH = 5.03), stir for 3 min, then add 48% by mass of water based on the mass of the obtained mixed powder, and then continue to stir for 2 min. Pour the obtained solidified soil into a mold, and after hardening and demolding, cure it naturally for 28 d to obtain solidified soil specimens. Then test the compressive strength (as Figure 5 shown) and anti-seepage performance (as Figure 3 shown) of the solidified soil specimens. In addition, test the contact angle (as Figure 6 shown) of the solidified soil specimens, and the test results are shown in the following table: .
[0050] Example 3: Preparation of a subgrade soil cementitious material curing agent, including the following steps: (1) Add polyaluminum sulfate powder with a fineness of 100 mesh to absolute ethanol at a ratio of 1 g: 20 ml, stir evenly, and then add γ-glycidoxypropyltrimethoxysilane and heptadecafluorodecyltriethoxysilane, where: the γ-glycidoxypropyltrimethoxysilane is 0.3% of the mass of the polyaluminum sulfate powder, and the heptadecafluorodecyltriethoxysilane is 0.8% of the mass of the polyaluminum sulfate powder. Then heat it to 60 °C under continuous stirring and keep it warm for 1.5 hours. After completion, filter out the solid matter to obtain the modified polyaluminum sulfate.
[0051] (2) Add the modified polyaluminum sulfate to water at a ratio of 1 g: 5 ml, then heat it to 60 °C with continuous stirring and keep it warm for 12 min. After completion, continue to heat it to 80 °C for evaporation to dryness until the weight of the remaining solid product no longer changes, thus obtaining the anti-seepage enhancer for standby.
[0052] (3) First, calcine the crushed granular coal gangue at 850 °C for 30 min, then cool it to room temperature after completion. Mix the calcined product with a sodium silicate solution with a mass fraction of 10% at a ratio of 1 g: 5 ml and stir evenly, then impregnate for 1 hour. After completion, filter out the particulate matter and dry it at 100 °C until the weight no longer changes to obtain coal gangue microparticles with a particle size distribution between 1 and 5 mm for standby.
[0053] (4) Weigh each component according to the following ratio: 200 parts by weight of 42.5 ordinary Portland cement, 130 parts by weight of the coal gangue microparticles of this example, 280 parts by weight of fly ash, 100 parts by weight of silica fume, 60 parts by weight of the anti-seepage enhancer of this example, 3 parts by weight of lignosulfonate water reducer, and 25 parts by weight of polyethylene fibers with a length of 20 mm. Mix the above components evenly by stirring to obtain the cementitious material curing agent.
[0054] Incorporate 20% of the mass of the cementitious material curing agent of this example into the dry acidic soil to be cured (pH = 6.51), stir for 3 min, then add 42% of the water of the mass of the obtained mixed powder, and then continue to stir for 2 min. Pour the obtained solidified soil into a mold, and after hardening and demolding, cure it naturally for 28 d to obtain solidified soil specimens. Then test the compressive strength (as Figure 7 shown) and anti-seepage performance (as Figure 3 shown) of the solidified soil specimens. In addition, test the contact angle of the solidified soil specimens, and the test results are shown in the following table: .
[0055] Example 4: Preparation of a subgrade soil cementitious material curing agent, including the following steps: (1) Add polyaluminum sulfate powder with a fineness of 180 meshes to absolute ethanol at a ratio of 1 g: 25 ml, stir evenly, and then add 0.22% of γ-aminopropyltriethoxysilane based on the mass of the polyaluminum sulfate powder. Then heat it to 70 °C with continuous stirring and keep it warm for 1 hour. After completion, filter out the solid matter to obtain modified polyaluminum sulfate.
[0056] (2) Add the modified polyaluminum sulfate to water at a ratio of 1 g: 8 ml, then heat it to 50 °C with continuous stirring and keep it warm for 10 min. After completion, continue to heat it to 100 °C for evaporation to dryness until the weight of the remaining solid product no longer changes, thus obtaining the anti-seepage enhancer for standby.
[0057] (3) Weigh the following components in the following proportions: 237 parts by weight of 42.5 ordinary Portland cement, 145 parts by weight of the coal gangue particles of the above Example 1, 300 parts by weight of fly ash, 120 parts by weight of silica fume, 65 parts by weight of the anti-seepage enhancer of this example, 4 parts by weight of polycarboxylate water reducer, and 28 parts by weight of polypropylene fibers with a length of 25 mm. Mix the above components and stir them evenly to obtain a cementitious material curing agent.
[0058] 25% of the cementitious material curing agent of this embodiment is added to the dry soil to be cured (pH=5.87), stirred for 3 minutes, and then 45% of the water of the mixed powder is added, and then stirred for 2 minutes. The obtained cured soil is poured into a mold, and after hardening and demoulding, it is naturally cured for 28 days to obtain a cured soil specimen. Then the compressive strength of the cured soil specimen is tested (such as Figure 8 as shown) and water resistance (as shown Figure 3 In addition, the contact angle of the solidified soil specimen was tested, and the test results are shown in the following table: .
[0059] Embodiment 5: A preparation method of a roadbed soil cementitious material curing agent comprises the following steps: (1) The crushed granular coal gangue is sieved to obtain coal gangue particles with a particle size distribution between 2 and 5 mm for later use.
[0060] (2) Weigh the following components in the following proportions: 237 parts by weight of 42.5 ordinary Portland cement, 145 parts by weight of the coal gangue particles of this embodiment, 300 parts by weight of fly ash, 120 parts by weight of silica fume, 65 parts by weight of the anti-seepage enhancer of the above embodiment 1, 4 parts by weight of polycarboxylate water reducer, and 28 parts by weight of polypropylene fibers with a length of 25 mm. Mix the above components and stir them evenly to obtain a cementitious material curing agent.
[0061] 25% of the cementitious material curing agent of this embodiment is added to the dry soil to be cured (pH=5.87), stirred for 3 minutes, and then 45% of the water of the mixed powder is added, and then stirred for 2 minutes. The obtained cured soil is poured into a mold, and after hardening and demoulding, it is naturally cured for 28 days to obtain a cured soil specimen. Then the compressive strength of the cured soil specimen is tested (such as Figure 9 as shown) and water resistance (as shown Figure 3 In addition, the contact angle of the solidified soil specimen was tested. The larger the contact angle, the better the hydrophobic impermeability. The test results are shown in the following table: .
[0062] Example 6: Preparation of a solidifying agent for subgrade soil cementitious material, comprising the following steps: (1) Add polyaluminum sulfate powder with a fineness of 100 meshes to absolute ethanol at a ratio of 1 g:20 ml. After stirring evenly, add γ-glycidyl ether oxypropyltrimethoxysilane and heptadecafluorodecyltriethoxysilane. Among them: the γ-glycidyl ether oxypropyltrimethoxysilane is 0.3% of the mass of the polyaluminum sulfate powder, and the heptadecafluorodecyltriethoxysilane is 0.8% of the mass of the polyaluminum sulfate powder. Then heat to 60 °C under continuous stirring and keep warm for 1.5 hours. After completion, filter out the solid matter, dry it to obtain an anti-seepage enhancer, and set it aside.
[0063] (2) Weigh each component according to the following ratio: 200 parts by weight of 42.5 ordinary Portland cement, 130 parts by weight of the coal gangue particles in the above Example 3, 280 parts by weight of fly ash, 100 parts by weight of silica fume, 60 parts by weight of the anti-seepage enhancer in this example, 3 parts by weight of lignosulfonate water reducer, and 25 parts by weight of polyethylene fibers with a length of 20 mm. Mix the above components and stir evenly to obtain a cementitious material solidifying agent.
[0064] Incorporate 20% of the mass of the cementitious material solidifying agent in this example into dry acidic soil to be solidified (pH = 6.51), stir for 3 min, then add 42% of the mass of water of the obtained mixed powder, and then continue to stir for 2 min. Pour the obtained solidified soil into a mold, and after hardening and demolding, cure it naturally for 28 d to obtain a solidified soil specimen. Then test the compressive strength (as Figure 10 shown) and anti-seepage performance (as Figure 3 shown) of the solidified soil specimen. In addition, test the contact angle of the solidified soil specimen, and the test results are shown in the following table: .
[0065] Example 7: Preparation of a solidifying agent for subgrade soil cementitious material, comprising the following steps: (1) First, calcine the crushed granular coal gangue at 700 °C for 45 min, cool it to room temperature after completion, mix the calcined product with clear water at a ratio of 1 g:20 ml, stir evenly, and then impregnate for 2 hours. After completion, filter out the particulate matter, dry it at 100 °C until the weight no longer changes to obtain coal gangue particles with a particle size distribution between 1 and 3 mm, and set it aside.
[0066] (2) Weigh each component in the following proportions: 275 parts by weight of 42.5 ordinary Portland cement, 160 parts by weight of the coal gangue particles of this embodiment, 400 parts by weight of fly ash, 142 parts by weight of silica fume, 78 parts by weight of the anti-seepage enhancer of the above-mentioned embodiment 2, 6.5 parts by weight of naphthalene-based water reducer, and 40 parts by weight of polyvinyl alcohol fibers with a length of 10 mm. Mix the above components and stir evenly to obtain the cementitious material curing agent.
[0067] Incorporate 30% of the mass of the cementitious material curing agent of this embodiment into the dry acidic soil to be cured (pH = 5.03). After stirring for 3 minutes, add 48% of the water of the mass of the obtained mixed powder, and then continue to stir for 2 minutes. Pour the obtained solidified soil into a mold, and after hardening and demolding, cure it naturally for 28 days to obtain solidified soil specimens. Then test the compressive strength (as Figure 11 shown) and anti-seepage performance (as Figure 12 shown) of the solidified soil specimens. In addition, test the contact angle of the solidified soil specimens, and the test results are shown in the following table: .
[0068] Example 8: The preparation of a subgrade soil cementitious material curing agent includes the following steps: Weigh each component in the following proportions: 200 parts by weight of 42.5 ordinary Portland cement, 130 parts by weight of the coal gangue particles of the above-mentioned embodiment 3, 280 parts by weight of fly ash, 100 parts by weight of silica fume, 3 parts by weight of lignosulfonate water reducer, and 25 parts by weight of polyethylene fibers with a length of 20 mm. Mix the above components and stir evenly to obtain the cementitious material curing agent.
[0069] Incorporate 20% of the mass of the cementitious material curing agent of this embodiment into the dry acidic soil to be cured (pH = 6.51). After stirring for 3 minutes, add 42% of the water of the mass of the obtained mixed powder, and then continue to stir for 2 minutes. Pour the obtained solidified soil into a mold, and after hardening and demolding, cure it naturally for 28 days to obtain solidified soil specimens. Then test the compressive strength (as Figure 13 shown) and anti-seepage performance (as Figure 12 shown) of the solidified soil specimens. In addition, test the contact angle of the solidified soil specimens, and the test results are shown in the following table: .
[0070] The above are only the preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or perform equivalent replacements for some of the technical features. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included within the protection scope of the present invention.
Claims
1. A roadbed soil cementitious material curing agent, characterized in that: The invention comprises the following components: 200-275 parts by weight of silicate cement, 130-160 parts by weight of coal gangue particles, 280-400 parts by weight of fly ash, 100-142 parts by weight of silica fume, 60-78 parts by weight of water-reducing agent, 3-6.5 parts by weight of water-reducing agent, and 25-40 parts by weight of fiber; wherein the water-reducing agent is prepared by the following method: (1) dispersing polyaluminium sulfate powder into anhydrous ethanol, then adding a silane coupling agent and a hydrophobic agent, and heating and keeping the mixture warm under stirring conditions; after completion, separating the solid matter to obtain modified polyaluminium sulfate; (2) adding the modified polyaluminium sulfate to water and heating and keeping the water warm under stirring conditions, and then evaporating to remove the water to obtain the anti-seepage enhancer.
2. The roadbed soil cementitious material curing agent according to claim 1, characterized in that: In step (1), the ratio of the polyaluminium sulfate powder to anhydrous ethanol is 1 g: 20-30 ml; Alternatively, in step (1), the fineness of the polyaluminium sulfate powder is 100-200 mesh.
3. The roadbed soil cementitious material curing agent according to claim 1, characterized in that: In step (1), the silane coupling agent is 0.15-0.3% of the mass of the polyaluminium sulfate powder; Alternatively, in step (1), the silane coupling agent includes at least one of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, and γ-methacryloxypropyltrimethoxysilane.
4. The roadbed soil cementitious material curing agent according to claim 1, characterized in that: In step (1), the hydrophobic agent is 0.5-0.8% of the mass of the polyaluminium sulfate powder; Alternatively, in step (1), the hydrophobic agent comprises at least one of tridecafluorooctyltrimethoxysilane, perfluorooctyltriethoxysilane, polyperfluoroalkylsiloxane, heptadecafluorodecyltriethoxysilane and hexamethyldisilazane; Alternatively, in step (1), the heating temperature is 60-70° C. and the insulation time is 1-1.5 hours.
5. The roadbed soil cementitious material curing agent according to claim 1, characterized in that: In step (2), the ratio of the modified polyaluminium sulfate to water is 1 g: 5-10 ml; Alternatively, in step (2), the heating temperature is 40-60° C. and the insulation time is 10-20 min; Alternatively, in step (2), the evaporation temperature is 80-100° C., and the evaporation is carried out at this temperature until the weight of the remaining solid product no longer changes.
6. The roadbed soil cementitious material curing agent according to claim 1, characterized in that: The coal gangue particles are processed by the following method: the granular coal gangue is calcined, and then immersed in a sodium silicate solution, and then the solid particles are separated and dried to obtain the obtained product.
7. The roadbed soil cementitious material curing agent according to claim 6, characterized in that: The calcination temperature is 700-850°C and the calcination time is 30-45 minutes; Alternatively, the ratio of the granular coal gangue to the sodium silicate solution is 1 g: 5-20 ml; Alternatively, the mass fraction of the sodium silicate solution is 4-10%; Alternatively, the immersion time is 1 to 2 hours; Alternatively, the particle size of the coal gangue particles is distributed between 1 and 5 mm.
8. The roadbed soil cementitious material curing agent according to any one of claims 1 to 7, characterized in that: The fiber includes: at least one of polyethylene fiber, polypropylene fiber, polyvinyl alcohol fiber, and polyacrylonitrile fiber; Alternatively, the length of the fiber is 10 to 25 mm; Alternatively, the water reducer includes at least one of a polycarboxylate water reducer, a naphthalene-based water reducer, and a lignin sulfonate water reducer.
9. The method for using the roadbed soil cement cementitious material curing agent according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing the dry acidic soil to be solidified with the solidifying agent evenly, and then adding water and stirring evenly.
10. The method of use according to claim 9, characterized in that: The amount of the curing agent is 20-30% of the mass of the soil to be cured; or, the water is 42-48% of the total mass of the soil to be cured and the curing agent; or, the pH of the soil to be cured is 5-6.5.
Citation Information
Patent Citations
Composite curing agent for concrete construction, and preparation method thereof
CN109265062A
Poaching-resistant powder coating composition
CN112708333A
Cement-free residue soil curing agent as well as preparation method and application thereof
CN115231892A
Solid waste-based composite curing agent and preparation method thereof
CN117602917A
Preparation method and application of waterproof impervious magnesium phosphate cement-based material
CN118206354A
Cited By
Preparation process of improved recycled concrete aggregate maritime work cement-based material
CN121225962A
Preparation process of improved recycled concrete aggregate marine cement-based material
CN121225962B
Preparation process of low-temperature fluid curing agent and stabilized soil building material prepared from low-temperature fluid curing agent
CN121248243A
Preparation process of low-temperature fluidized curing agent and cured earth building material thereof
CN121248243B
Solid waste-based foundation pit muck solidifying agent and construction method thereof
CN122647197A